Performance of Acquisitions of Distressed Firms - Bruton, Garry D.; Oviatt, Benjamin M.; White, Margaret A. (Academy of Management Journal, 1994)
In 51 acquisitions of financially distressed firms, related business combinations in which the acquirers had prior acquisition experience performed best. However, business relatedness and acquisition experience had no effect on performance in a control group of 46 acquisitions of firms that were not distressed. The results imply that tacit knowledge about the acquisition process and about how to integrate and manage the assets of distressed firms may be keys to their successful acquisition.